Case Report: Recurrent Variant c.298 TA in CCN6 Gene Found in Progressive Pseudorheumatoid Dysplasia Patients From Patni Community of Gujarat: A Report of Three Cases - Sheth, Harsh; Shah, Jhanvi; Nair, Aadhira; Naik, Premal; Sheth, Jayesh (Frontiers in Genetics, 2021)
Biallelic mutations in the CCN6 gene are known to cause a rare genetic disorder- progressive pseudorheumatoid dysplasia (PPD). PPD is characterized by distinct joint deformities of interphalangeal joints, stiffness, gait disturbance, abnormal posture and absence of inflammation, resulting in significant morbidity. Largest case series of PPD from India suggests c.233G>A and c.1010G>A to be the most common mutations in the CCN6 gene, although distribution of these variants amongst endogamous communities in India has not been carried out. We here report 3 cases of PPD from 3 independent families belonging to the Patni community of Gujarat, a community known to practice endogamy. All 3 cases had short stature, gait disturbance, scoliosis and interphalangeal joint deformities. Analysis by whole exome sequencing in the first case showed presence of a previously known, homozygous, missense variant c.298T>A (p.Cys100Ser) in exon 3 of the CCN6 gene in all cases. Due to all 3 families belonging to the same community, analysis by Sanger sequencing in the remaining 2 cases for the aforementioned variant showed both cases to be of homozygous mutant genotype. Unaffected family members, i.e. parents and siblings, were either heterozygous carriers or wildtype for the said variant. The present case series is the first report of a recurrent variant occurring across multiple PPD affected individuals from unrelated families belonging to the same community from India.